The Impact of Student Attitude on Information, Communication, Creation Skills and Student Engagement - Xin, Ho Khai; Ping, Ng Junn; Tong, Liu Xiao; Yan, Kua Mei; Abdul Razak, Norfadzilah (Information Management and Business Review, 2024)
The Malaysian education system is guided by the Malaysia Education Blueprint, which drives the overall quality and effectiveness of education in the country. This study provides insights and assists in forming informed guidelines for the Ministry of Education regarding the impact of skill factors. The relationship between the direct effects of these three primary skills and attitudes is supported by Self-Efficacy Theory (SET). The indirect relationship, where attitude mediates the effects of these skills on student engagement, is supported by Self-Determination Theory (SDT) and Social Cognitive Theory (SCT). A questionnaire was distributed to local university students currently in their fourth semester and analyzed using the Structural Equation Model using Partial Least Square (PLS). The structural model results direct relationship between attitude and student engagement and between information skills and attitude. In addition, the mediation analysis shows that the relationship between information skills and student engagement, mediated by student attitude, was significant. Based on these results, it is recommended that the Ministry of Education focus on providing supportive resources, such as learning environments and training for educators, in the upcoming Malaysia Education Blueprint for 2026 to 2036. Additionally, offering Digital Literacy Programs to equip students with information skills can positively influence student attitudes and thereby increase the level of student engagement, which is crucial for improving the academic performance and achievement of Malaysia’s educational system. Future research should include a cross-cultural comparison to reconsider educational theories for Asian countries, as many theories are currently based on Western educational settings and contexts.